Global Risk Sharing Through Trade in Goods and Assets: Theory and Evidence - Inga Heiland (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Firms facing uncertainty about demand at the time of production expose their shareholders to volatile returns. Risk-averse investors trading multiple assets will favor stocks that tend to yield high returns in bad times, that is, when marginal utility of consumption is high. In this paper, I develop a firm-level gravity model of trade with risk-averse investors to show that firms seeking to maximize their present value will take into account that expected profits on a given destination market will be discounted by shareholders depending on the correlation with their expected marginal utility of consumption. The model predicts that, ceteris paribus, firms sell more to markets where profits covary less with the income of their investors. To test this prediction empirically, I use data on stock returns to estimate the correlation between demand growth in destination markets with expected marginal utility growth of investors in the home country. Then, I use bilateral trade data to test whether exports to markets where demand tends to be high at times when investors' expected marginal utility of consumption is high are larger compared to sales on markets where demand tends to be high at times when investors in the home country are well off anyway.
Keywords: F12; F36; G15; 330